2021
DOI: 10.1038/s41598-021-92257-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical reservoir computing with origami and its application to robotic crawling

Abstract: A new paradigm called physical reservoir computing has recently emerged, where the nonlinear dynamics of high-dimensional and fixed physical systems are harnessed as a computational resource to achieve complex tasks. Via extensive simulations based on a dynamic truss-frame model, this study shows that an origami structure can perform as a dynamic reservoir with sufficient computing power to emulate high-order nonlinear systems, generate stable limit cycles, and modulate outputs according to dynamic inputs. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…The reservoir is also evaluated with emulation tasks. The nonlinear auto-regressive moving average (NARMA) time series is used to test whether the reservoir possesses adequate nonlinearity and long time lags 4 , 24 , 26 , 28 . These tasks show the multi-tasking capability of the reservoir.…”
Section: Benchmark Tasks For Hopf Prcmentioning
confidence: 99%
See 2 more Smart Citations
“…The reservoir is also evaluated with emulation tasks. The nonlinear auto-regressive moving average (NARMA) time series is used to test whether the reservoir possesses adequate nonlinearity and long time lags 4 , 24 , 26 , 28 . These tasks show the multi-tasking capability of the reservoir.…”
Section: Benchmark Tasks For Hopf Prcmentioning
confidence: 99%
“…( 13 ), is the target of the system. n is the order of NARMA task, , and 26 , 28 . u ( t ) is the continuous input that is used to force the Hopf PRC, which is a function of a three sinusoidal functions.…”
Section: Benchmark Tasks For Hopf Prcmentioning
confidence: 99%
See 1 more Smart Citation
“…This paradigm entails using a high-dimensional, nonlinear dynamical (physical) system as a computational resource to solve a task. Examples encompass the control of mechanical systems by using a compliant robot body 14 , the processing of optical 15 and electrical 16 signals, or quantum reservoir computers 17 . In one particular case, a water bucket was used as a physical reservoir to build a liquid computer that could solve the XOR-problem 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka et al demonstrated a method for identifying the direction of a wind stream from the movement of a soft flapping wing measured by flexible strain sensors as PRC. [ 21 ] An increasing number of PRC applications has been recently proposed for many different soft robotic platforms, such as tensegrity structures, [ 22 ] quadruped robots, [ 23 ] pneumatically driven systems, [ 24,25 ] fish robots, [ 26 ] origami robots, [ 27 ] and so on. In these examples, because the computational load is mainly outsourced to the physical body, we can expect to see savings in information processing.…”
Section: Introductionmentioning
confidence: 99%